1996
DOI: 10.1353/rhe.1996.0005
|View full text |Cite
|
Sign up to set email alerts
|

G. Stanley Hall and the Study of Higher Education

Abstract: The centenary of higher education as a field of study occurred in 1993, commemorating the first course in higher education, offered in the autumn of 1893 at Clark University by G. Stanley Hall. This course also launched the first higher education program, for by 1924, three professors had offered 16 courses, written numerous publications, and advised the first 10 master's and doctoral students. This article reviews Hall's professional life, his concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Although higher education studies covering administration, *Corresponding author. Email: Peter.Kandlbinder@uts.edu.au pedagogy and public policy have existed in formal courses in the US since the 1890s (Goodchild, 1996), McKeachie (1997) found that pre-service training before commencing teaching in universities is rare. In Australia, the earliest example of training for university teaching was the Graduate Diploma of Tertiary Education at the Darling Downs Institute of Advanced Education (later the University of Southern Queensland) in the late 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…Although higher education studies covering administration, *Corresponding author. Email: Peter.Kandlbinder@uts.edu.au pedagogy and public policy have existed in formal courses in the US since the 1890s (Goodchild, 1996), McKeachie (1997) found that pre-service training before commencing teaching in universities is rare. In Australia, the earliest example of training for university teaching was the Graduate Diploma of Tertiary Education at the Darling Downs Institute of Advanced Education (later the University of Southern Queensland) in the late 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…That course, college and university problems in the United States and Europe focused on the evolving role of colleges and universities in a modernizing world (Goodchild, 1996). Hofsteader (1960) named this era from the 1890s into World War I as the age of reform, and this age did not escape institutions of higher learning.…”
Section: Prior Studies Of Higher Education Doctoral Program Curriculummentioning
confidence: 99%
“…He admitted her, taught her courses, recommended her for employment, and eventually published her article, based on her thesis, in his Pedagogical Seminary. 141 As university historian William Koelsch stated, Hall's actions enabled Clark to be "ahead of Hopkins and Harvard" in admitting women, while "behind Yale and Chicago." 142 Clark thus reflected a group of New England institutions in 1911 that allowed some women admission, such as, Tufts College with its 691 men and 105 women (or 15 percent) or the University of Vermont with its 479 men and 58 women (or 12 percent), but unlike Middlebury College with its 115 men and 107 women (or 93 percent) or Boston University with its 756 men and 631 women (or 83 percent).…”
Section: Becoming the National Spokesperson For The New Education As mentioning
confidence: 99%